Electrochemistry and electrocatalysis of a Pt@poly(neutral red) hybrid nanocomposite. (20th July 2015) - Agrisuelas, J.; García-Jareño, J.J.; Rivas, P.; Rodríguez-Mellado, J.M.; Vicente, F.
Highlights: Pt nanoparticles are electrodeposited on poly(neutral red) film Composite was studied by Vis-NIR spectroelectrogravimetry and ac -electrogravimetry Pt stabilizes polarons of inter-monomer bonds of film Polarons are the electrocatalytic sites Poly(neutral red) acts as a proton and electron reservoir for H2 O2 reduction. Abstract: Platinum nanoparticles have been deposited on a scaffold of electrosynthetized phenazine-type polymer, the poly(neutral red). This work discusses the role of poly(neutral red) in the electrochemistry and electrocatalysis properties of the hybrid nanocomposite. In situ combination of electrochemical quartz crystal microbalance and visible-near infrared spectroscopy (cyclic Vis-NIR spectroelectrogravimetry) and a combination of electrochemical impedance spectroscopy and mass impedance spectroscopy ( ac -electrogravimetry) were employed. Two electrochemical processes have been identified in our experimental conditions. On the one hand, the radical cations (polarons) localized in the inter-monomer bonds of poly(neutral red) are identities stabilized by platinum nanoparticles. The polaron charge is balanced by the relative slow transfer of anions between the hybrid nanocomposite and solution. On the other hand, a relative fast transfer of cation (but not H3 O + ) is involved in the second electrochemical process. H2 O2 was used as the target analyteto study the electrocatalytic reaction. The hybrid nanocomposite catalyzes the H2 O2 reduction in phosphate buffer solutions at neutral pH . Polarons have been identified as the electrocatalytic sites. Poly(neutral red) would act as a proton reservoir used during the H2 O2 reduction. The excellent electrocatalytic response and the knowledge of its electrochemical mechanism can help to developbiosensors for other analytes which react with radical species.